PENGGUNAAN MEDIA FLASHCARD DALAM PEMBELAJARAN KOSAKATA PADA KETERAMPILAN BERBICARA SISWA MTsN 2 ACEH BESAR - Falah, Moch Fajarul; Banurea, Nurmajidah Rizky (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2024)
Vocabulary is an important linguistic element. So vocabulary mastery for students becomes absolute. Most of the eighth grade students at MTsN 2 Aceh Besar have difficulty remembering and understanding vocabulary. This has an impact on poor mastery of speech skills. This qualitative research aims to analyze the role of flashcard media in improving students' memory and vocabulary comprehension, which is generated from data from field observations and interviews, and to link it to previous research findings related to flashcard media from journal articles and others. The results of this research are that using flashcard media can improve students' memory and understanding of Arabic vocabulary, making it easier to practice speaking skills.